Polymorphisms in Tunisian patients with N-acetylgalactosamine-6-sulfate sulfatase gene deficiency: Implication in Morquio A disease - Chkioua Latifa; Khedhiri Souhir; Ferchichi Salima; Miled Abdelhedi; Laradi Sandrine (BMC, 2011)
Abstract Mucopolysaccharidosis type IVA or Morquio A syndrome is characterized by the lack of N-acetylgalactosamine-6-sulfate-sulfatase and the accumulation of keratan sulfate and chondroitin-6-sulfate in the lysosomes. At least, 148 mutations and 16 polymorphisms were identified in the GALNS gene. The aim of this study was the screening of polymorphisms within 7 patients recruited from many regions of Tunisia in order to determine the haplotypes and their association with the mutations previously reported. Patients and methods We have used the PCR sequencing to analyse the different haplotypes and to identify the polymorphisms within 7 affected MPS IVA patients. Results Nine GALNS polymorphisms were detected in the 7 studied patients. Five of these polymorphisms are within the GALNS gene exons. Six polymorphisms have been previously described and used for linkage analysis in MPS IVA patients and determination of haplotypes. We have identified two novel heterozygous polymorphisms in intron 13 and intron 3 Conclusion Polymorphisms may be useful for carrier detection and prenatal diagnosis in informative families whose specific mutations have not been identified. The determination of haplotypes can also determine the origin of some mutations in a population.